Inhibitory Abilities of Bacillus Isolates and Their Culture Filtrates against the Gray Mold Caused by Botrytis cinerea on Postharvest Fruit - Chen, Xiaomeng; Wang, Yajie; Gao, Yu; Gao, Tongguo; Zhang, Dongdong (The plant pathology journal, 2019)
Botrytis cinerea, a major phytopathogenic fungus, has been reported to infect more than 200 crop species worldwide, and it causes massive losses in yield. The aim of this study was to evaluate the inhibitory abilities and effects of Bacillus amyloliquefaciens RS-25, Bacillus licheniformis MG-4, Bacillus subtilis Z-14, and Bacillus subtilis Pnf-4 and their culture filtrates and extracts against the gray mold caused by B. cinerea on postharvest tomato, strawberry, and grapefruit. The results revealed that the cells of Z-14, culture filtrate of RS-25, and cells of Z-14 showed the strongest biocontrol activity against the gray mold on the strawberry, grape, and tomato fruit, respectively. All the strains produced volatile organic compounds (VOCs), and the VOCs of Pnf-4 displayed the highest inhibition values. Based on headspace solid-phase microextraction in combination with gas chromatography-mass spectrometry, esters accounted for the largest percentage of the VOCs produced by RS-25, MG-4, Z-14, and Pnf-4 (36.80%, 29.58%, 30.78%, and 36.26%, respectively). All the strains showed potent cellulase and protease activities, but no chitinase activity. RS-25, Z-14, and MG-4, but not Pnf-4, grew on chrome azurol S agar, and an orange halo was formed around the colonies. All the strains showed biofilm formation, fruit colonization, and lipopeptide production, which may be the main modes of action of the antagonists against B. cinerea on the fruit. This study provides the basis for developing natural biocontrol agents against the gray mold caused by B. cinerea on postharvest fruit.Botrytis cinerea, a major phytopathogenic fungus, has been reported to infect more than 200 crop species worldwide, and it causes massive losses in yield. The aim of this study was to evaluate the inhibitory abilities and effects of Bacillus amyloliquefaciens RS-25, Bacillus licheniformis MG-4, Bacillus subtilis Z-14, and Bacillus subtilis Pnf-4 and their culture filtrates and extracts against the gray mold caused by B. cinerea on postharvest tomato, strawberry, and grapefruit. The results revealed that the cells of Z-14, culture filtrate of RS-25, and cells of Z-14 showed the strongest biocontrol activity against the gray mold on the strawberry, grape, and tomato fruit, respectively. All the strains produced volatile organic compounds (VOCs), and the VOCs of Pnf-4 displayed the highest inhibition values. Based on headspace solid-phase microextraction in combination with gas chromatography-mass spectrometry, esters accounted for the largest percentage of the VOCs produced by RS-25, MG-4, Z-14, and Pnf-4 (36.80%, 29.58%, 30.78%, and 36.26%, respectively). All the strains showed potent cellulase and protease activities, but no chitinase activity. RS-25, Z-14, and MG-4, but not Pnf-4, grew on chrome azurol S agar, and an orange halo was formed around the colonies. All the strains showed biofilm formation, fruit colonization, and lipopeptide production, which may be the main modes of action of the antagonists against B. cinerea on the fruit. This study provides the basis for developing natural biocontrol agents against the gray mold caused by B. cinerea on postharvest fruit.